PGE2 in fibrosis and cancer: Insights into fibroblast activation - Elwakeel, Eiman; Brüne, Bernhard; Weigert, Andreas (Prostaglandins & other lipid mediators, 2019)
•Fibroblasts are the main cells of connective tissue and participate in wound repair upon activation.•Unchecked fibroblast activation leads to fibrosis and contributes to cancer development.•PGE2 restricts fibroblast activation in fibrosis, thereby acting in an anti-fibrotic manner.•While PGE2 is considered a tumor-promoting lipid, its role in cancer-associated fibroblast activation is unclear. Fibroblasts are the essential cellular architects of connective tissue and as such are crucial cells in contributing to organ homeostasis. While fulfilling important repair functions during tissue regeneration upon wounding, chronic fibroblast activation provokes pathological organ fibrosis and promotes neoplastic disease progression. Identifying targets that may serve to therapeutically terminate fibroblast activation is therefore desirable. Among the mediators that may be relevant in this context is the prostanoid prostaglandin E2 (PGE2) that is produced during inflammatory settings, where pathological fibrosis occurs. Here, we summarize current, in part controversial, concepts on the impact of PGE2 on fibroblast activation in fibrotic diseases including cancer, and discuss these findings in the context of the evolving concept of fibroblast heterogeneity.